Pembuatan biodiesel biji kepuh (Sterculia Foetida L.) dengan proses alkoholisis dengan katalisator buangan proses perengkahan minyak bumi pertamina unit II Palembang - Roni, Kiagus Ahmad (Jurnal Dinamika Penelitian Industri, 2012)
Kepuh (Sterculia foetida L.) seed oil is not utilized yet. Therefore, it should beprocessed to produce valuable product. One of the possible methods is alcoholysis with wasted solid catalyst obtained from Pertamina Unit II located in Palembang, as catalyst. With this process some benefits might be obtained from these wastes. The alkoholysis of kepuh seed oil with etanol and reactivated used solid catalyst at higher pressure was accomplished in an autoclave provided with manometer, thermometer, sampling device, heater, and mixer. The experiment was started by filling the autoclave with kepuh seed oil, alcohol, and the catalyst, then the heater and the mixer were switched on. Samples were taken out at 10 minutes intervals, and after being separated, the bottom layer was analyzed in order to determine its glycerol content using acetin method. By raising the temperature, catalyst concentration, rate of mixing, and ethanol-oil ratio, the glyceride conversion increased. From the value of k" , Reynolds index, the change of k" value with 10°C increase of temperature, and the value of the activation energy, it seemed that chemical reaction controlled the process. The alcoholysis of kepuh seed oil followed pseudo first order reaction with respect to the glyceride concentration. The equation of the reaction rate constant, k" , can be presented as : k" = 1659.21.52 e-4668.74/T {7.4976(10-3) + 4.6455(10-3)H} N 0.0529 P 0.1824 , with an experunental error ± 13.66 % for k" , and a deviation of x of ± 8.89 %. The relative favorable process conditions, were 60 minutes of reaction time, temperature of 110°C, catalyst concentration of 2 %, mixing velocity of 310 rpm, and alcohol-oil ratio of 6 mgek/mgek. Under this a condition the conversion was 70.91Keywords : Biodiesel, Kepuh, alkoholysis, wasted catalyst AbstrakMinyak biji kepuh (Sterculia foetida L.) belum banyak dimamfaatkan. Oleh karena itu, minyak biji kepuh ini perlu diolah, antara lain dengan proses alkoholisis, memakai katalisator buangan perengkahan minyak bumi Pertamina Unit II Palembang, yang juga merupakan limbah, agar dapat dimamfaatkan. Alkoholisis minyak biji kepuh pada tekanan lebih dari satu atmosfer dengan katalisator buangan perengkahan minyak bumi Pertamina Unit II Palembang, dijalankan dalam reaktor yang berupa autoklaf, yang dilengkapi dengan manometer, termometer, kran pengambil cuplikan, pemanas, dan pengaduk. Mula-mula autoklaf diisi minyak biji kepuh, alkohol, dan katalisator denganjumlah tertentu, lalu pemanas dan pengaduk dihidupkan dan diatur. Cuplikan diambil pada setiap selang waktu 10 menit dan selanjutnya lapisan bawah dianalisis kadar gliserolnya dengan cara asetin. Pada kisaran tertentu, peningkatan suhu, persentase katalisator, kecepatan putaran pengaduk, dan perbandingan etanol-minyak, mengakibatkan konversi gliserid bertambah. Berdasarkan nilai k", indeks Reynolds, perubahan nilai k" untuk setiap kenaikan suhu 10 °C, dan nilai tenaga pengaktif, ternyata reaksi kimialah yang mengendalikan kecepatan reaksi keseluruhan. Alkoholisis minyak biji kepuh mengikuti reaksi orde satu semu terhadap gliserid. Tetapan kecepatan reaksi k" mempunyai persamaan k" = 1659,2152 e -4668,74/ T (7,4976.10-3 + 4,6455.10-3H) N 0,0529 P 0, 1824 dengan ralat rata-rata hasil percobaan terhadap persamaan sebesar ± 13,66 % untuk k", dan penyimpangan x ± 8,89 %. Keadaan proses yang relatif baik, dijumpai pada waktu 60 menit, suhu 110 °C, persentase katalisator 2 %, kecepatan pengadukan 310 ppm, dan perbandingan alkohol-minyak 6 mgek/mgek. Pada keadaan itu konversi mencapai 0.7091 bagian.Kata Kunci : Biodiesel, kepuh, alkoholisis, katalis buangan